Optimization of CPU Heatsink Design, A Simulation-Based Study on Temperature Distribution with Different Fin Number - Setiawan, Dona; Priyanto, Agung; Ma'arif, Samsul; Rizkyanto Putra, Okta (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2026)
In this era of digitalization, a fast processor (CPU) is needed to meet computing needs, but a fast processor can produce high temperatures. With the water cooling technique, the heatsink can help in cooling the processor with the help of a blower/fan. A numerical study was conducted to review the temperature distribution in the heatsink with perforated fin, the effect of the number of holes, and the effect of inlet speed on the CPU temperature, in this study regular fin and perforated fin with 10, 20, and 30 were used. CPU performance relies heavily on an effective thermal management system, where the heatsink plays an important role in dissipating excess heat. This study aims to optimize the design of the CPU heatsink by analyzing the effect of the number of fins on temperature distribution. Simulations were performed using computational software to evaluate multiple heatsink models with varying numbers of fins under the same thermal load conditions. The observed parameters include maximum temperature, heat flux, and temperature distribution on the surface of the heatsink. The simulation results show that an optimal number of fins can significantly improve heat dissipation performance, while an excessive number of fins can actually inhibit airflow and decrease thermal efficiency. This study provides an overview of the thermal behavior of heatsinks and becomes a reference in designing more efficient cooling systems for electronic devices.